CO$_{2}$ Gas Sensing Using Optical Fiber Fabry–Perot Interferometer Based on Polyethyleneimine/Poly(Vinyl Alcohol) Coating - Wenwen Ma; Ruohui Wang; Qiangzhou Rong; Zhihua Shao; Wenlu Zhang; Teng Guo; Jie Wang; Xueguang Qiao (IEEE Photonics Journal)
An optical fiber Fabry–Perot interferometer (FPI) based on poly (ethyleneimine) (PEI)/ poly (vinyl alcohol) (PVA) blend membrane is proposed and realized experimentally as a sensor for the pressure of CO $_{2}$ in the atmosphere. The functional material layer based on PEI/PVA blend polymer exhibits reversible optical path difference change because of absorption and release of CO $_{2}$ gas molecules. The cavity of the FPI is fabricated by coating a 15- $μ$ m PEI/PVA blend film on the end-face of a cleaved single-mode fiber. An interference spectrum with fringe contrast of 19.5 dB and free spectra range of 33.15 nm is obtained. The proposed FPI sensor is sensitive to the changes of concentration of CO $_{2}$ , as well as a sensitivity of 0.281 nm/ $%$ within an interval which ranges from 7.6 $%$ to 86.9 $%$ .